Toplumsal Ölçeğin Uyarlanması: Geçerlik ve Güvenirlik Çalışmaları - (:unkn) unknown (My University, 2004)
Bu araştırmada, Toplumsal ilgi Ölçeği' nin (TÎÖ) Türkçe'ye uyarlanması ve aracın geçerlik, güvenirlik çalışmaları yapılmıştır. 400 üniversite öğrencisi bu çalışmada yer almıştır. Ölçek, 52 maddeli Likert tipi bir ölçeltir. Ölçeğin güvenirliği, Cronbach Alfa iç tutarlık kat¬sayısı ve testin tekrarı yöntemleriyle, geçerliği ise, kapsam geçerliği ve faktör analizi yolu ile hesaplanmıştır. Faktör analizi sonucu, ölçeğin tek boyutlu olduğunu göstermiştir. Yapılan çalışmalar sonrası elde edilen bulgular, TtÖ' nin Türk üniversite öğrencileri üzerinde geçerli ve güvenilir olarak kullanılabileceğini göstermektedir.

Adaptation of Social Interest Index (SlI) to The Türk culture and Its Reliability and Validity tn the present investigation the Turkish adaptation and the reliability and validity Studies of the Social Interest Index (SİÎ). The sample consisted of 400 undergraduates (girls and boys) from the Faculty of Education, Marmara University, Istanbul. Index used in the research was 52-item Likert-type revised "Social Interest Index" with 5-point response format. For reliability, Cronbach Alpha internal con¬sistency and test-retest, and for validity, content validi¬ty and factor analysis were utilized. Factor analysis indicated that the revised Social Interest Index might be taken as a one-dimension scale. Finding show that this index can be used with acceptable level of validity and reliability for Turkish undergraduate students
Adaptation of Social Interest Index (Sİİ) to the Türk Culture and its Reliability and Validity